Selective solidarity – a critical analysis of Spanish and Polish asylum policies in the face of overlapping migration crises - Ahmad Torres, Sara (Kortowski Przegląd Prawniczy, 2025)
This article compares governments of Spain and Poland responses to refugee crisis in the 2015 and the ongoing Ukrainian displacement. The text critiques the fact that the EU’s Temporary Protection Directive 2001/55/EC was not activated in 2015, but it has been applied to Ukrainians (and persons granted refugee status in Ukraine) and their family members. Spain shifted from limited intake in 2015 to proactive support for Ukrainians, while Poland moved from an anti-refugee stance to welcoming persons from Ukraine. Analysis of national and the EU’s norms made it possible to identify gaps in Directive and stress the need to clarify criteria for granting protection and equitable burden-sharing in order to ensure consistent, long-term support for displaced populations.